Hybrid Freeze-Dried Dressings Composed of Epidermal Growth Factor and Recombinant Human-Like Collagen Enhance Cutaneous Wound Healing in Rats - Cheng, Yating; Li, Yangfan; Huang, Shiyi; Yu, Fenglin; Bei, Yu; Zhang, Yifan; Tang, Jianzhong; Huang, Yadong; Xiang, Qi (Frontiers in Bioengineering and Biotechnology, 2020)
Epidermal growth factor (EGF) is important for promoting skin repair and remodelling. Native collagen is also widely used as a scaffold for skin tissue engineering. The limitations of EGF include easy decomposition or inactivation, while native collagen is immunogenic and has poor solubility. Therefore, we constructed a freeze-dried dressing based on the recombinant human-like collagen (RHC) to act as a carrier for EGF (RHC/EGF freeze-dried dressing) and promote skin wound closure. Here, the freeze-dried dressing that combined EGF and RHC significantly enhanced the proliferation, adhesion, and spreading of NIH/3T3 fibroblasts and migration of HaCaT keratinocytes at the wound site. The physicochemical characteristics of the RHC/EGF freeze-dried dressing investigated using scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and differential scanning calorimetry (DSC) revealed that it was a loose and porous cake that redissolved quickly. The molecular mechanisms involved in cell proliferation and angiogenesis were also assessed. The expression levels of the markers Ki-67, proliferating cell nuclear antigen (PCNA), vascular endothelial growth factor (VEGF), and cluster of differentiation 31 (CD31) were significantly increased after treatment with the RHC/EGF freeze-dried dressing (P<0.01, vs RHC or EGF alone). This increase indicated that the RHC/EGF freeze-dried dressing significantly accelerated wound closure, re-epithelialisation, and the orderly arrangement and deposition of collagen in the Sprague-Dawley rats with full-thickness skin defects. This work describes a significant step toward the development of wound environments conducive to healing, and the RHC/EGF freeze-dried dressing is a potential therapeutic strategy in wound management.